A SEMIOTIC ANALYSIS MYTH OF LIFE IN LYRIC’S BLOWIN’IN THE WIND BY BOB DYLAN’S - Myrna, Myrna Nur Sakinah; Aufa almujafar, Muhammad Ghifar (TEXTURA, 2020)
This research analyzes the myths that exist in the lyrics of "Blow in the wind" by Bob Dylan. Researcher used descriptive qualitative methods because the results of this study were words that were then discussed. Lyrics of Bob Dylan’s "Blow in the wind" research are like wind, humans, sky, mountains, seas, humans, cannon balls. This study uses Roland Barthes’ theory and focuses on the denotative, connotative and mythical meanings of Bob Dylan’s "Blow in the wind" lyrics. The results in this study provide an understanding of the life and culture of mankind from now on, besides the results of this study provide historic results and find some thoughts about how human life. One form of myth that is in this study is through the word wind, wind in this study has a myth about the answers to the problems of human life. The problems of human life are war, poverty, and suffering. This song is a form of protest against war, the war which discusses in the lyrics of this song is about war, Vietnam, the government only focuses on war and is discussing about African-Americans who use civil rights in Vietnam war. The song lyrics that have to be questioned in the lyrics of this song are very difficult to solve just like seeing the wind or maybe the meaning of the wind here also means that people do not care more about the problems that arise and only need.